THE DISTINCTIVE CHARACTER IN THE MODERNIZATION OF ISLAMIC EDUCATION THROUGH CURRICULUM AND LEARNING MANAGEMENT - Minarti, Sri; Rohimiya, Firda Sibtur; Wardi, Moh. (Nurul Jadid University, 2022)
In management and institutional development, modification of the Islamic education curriculum is a must because of the times' demands and globalization's development. Therefore, pesantren need curriculum and learning management that follows the needs of the times and becomes a bridge for achieving the vision and mission of the institution. This article seeks to understand the form of curriculum and learning management in the context of modernizing the education and learning governance system in line with the times at Tarbiyatul Mu'allimien Al-Islamiyah (TMI) Al-Amien Prenduan. The approach used in this study is a qualitative research approach with a case study type of research. At the same time, the data analysis technique used in this study is the data analysis technique of Miles, Huberman, and Saldana, which consists of data condensation, data display, and data verification. The results of the study show that the distinctiveness of the modernization of Islamic educational institutions through curriculum management and learning at Tarbiyatul Mu'allimien Al-Islamiyah (TMI) Al-Amien Prenduan is carried out through external benchmarking activities in the fields of curriculum development and learning, curriculum development and program variations, and organizing education compelling character. The application of curriculum and learning management at TMI Wanita Al-Amien Prenduan also refers to three essential activities in students' daily lives. These activities are organized into intra-curricular, extra-curricular, and co-curricular activities.